2012
DOI: 10.3176/proc.2012.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cellulose content on thermal properties of poly(lactic) acid/cellulose and low-density polyethylene/cellulose composites

Abstract: Crystallization behaviour of polylactic acid/cellulose (PLA/CELL) and linear low-density polyethylene/cellulose (LDPE/CELL) composites was studied by differential scanning calorimetry (DSC) and polarized light microscopy equipped with hot-stage. The effect of addition of cellulose on thermal properties of PLA/CELL and LDPE/CELL composites was considered. The DSC experiments were performed at different scanning rates.For pure PLA the crystallization peak at r= 98.8 °C was observed in DSC scans at 20°C/min with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…The results reveal a sharp reduction in the percentage crystallinity from about 58% for pure LDPE to about 11% at a MCC concentration of 30 wt% within the matrix. This reduction in the percentage crystallinity agrees with what Šumigin et al 23 and Sdrobis et al 21 reported in their work.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results reveal a sharp reduction in the percentage crystallinity from about 58% for pure LDPE to about 11% at a MCC concentration of 30 wt% within the matrix. This reduction in the percentage crystallinity agrees with what Šumigin et al 23 and Sdrobis et al 21 reported in their work.…”
Section: Resultssupporting
confidence: 92%
“…This outcome contradicts with what was stated by Tajeddin et al 1 and Sdrobis et al, 21 where the authors confirmed that melting temperatures of LDPE/cellulose composites increase as the concentration of cellulose increases. Pasquini et al, 22 Šumigin et al, 23 and Pöllänen et al 24 stated in their publications that the crystallization and melting temperatures for pure LDPE will be almost as same as with LDPE adopted by cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…the -F groups of the polymer chain). So, the degree of crystallinity of the blend matrix increases with the addition of HPC [29]. As can observe, the T g and T m are affected by the HPC content in the blend showing that the polymers are miscible.…”
Section: 22mentioning
confidence: 84%
“…203 Of particular interest are PLA composites reinforced with cellulose. 204 It has been demonstrated that the cellulose particles behave as nucleating agents, and therefore increase the cold crystallinity of the final composite. 204 As demonstrated in previous studies, the modification of cellulose is crucial in order to obtain significant improvements in mechanical properties.…”
Section: Polysaccharidesmentioning
confidence: 99%